(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The case study describes the cause of an increase in mortality rates among 35-day-old broilers that developed respiratory distress and bloody diarrhea on a farm in Malaysia. Materials and Methods: The organ samples were subjected to laboratory testing and postmortem inspection. Escherichia (E.) coli and Mycoplasma (M.) gallisepticum were detected using bacterial isolation and molecular diagnostics using polymerase chain reaction. Results: Chickens with the infection had widespread fibrin buildup in several organs and hemorrhages on the duodenal mucosa. Additional histology and laboratory analysis of organ samples revealed infection with M. gallisepticum, E. coli, and enteric Eimeria spp., all of which are consistent with complex chronic respiratory disease (CCRD) associated with coccidiosis. Tylosin tartrate 20% (w/w) (2.5 gm/l) was prescribed for 1 week along with a combination of the broad-spectrum bacteriostatic drug streptomycin (25 mg/kg) and coccidiostat (2 gm/5 l). Conclusion: CCRD and coccidiosis are both infectious diseases that can infect chicken flocks, resulting in production losses and carcass quality degradation. Early disease detection and proper treatment should be provided promptly, and tight farm biosecurity should be implemented to prevent chicken mortality on the farm, as was achieved successfully. J. Adv. Vet. Anim. Res., 8(4): 576-580, December 2021 http://doi.org/10.5455/javar.2021.h547